Case study: implementation of health education in RSU Kabupaten Tangerang as a result of Problem Solving for Better Health (PSBH) in 2018 - Tatiana Siregar; Misparsih Misparsih; Jaenudin Saputra (Universitas Muhammadiyah Tangerang, 2019)
Health education is an activity that is often carried out by health workers, especially nurses. The process of implementing health education needs to be understood by nurses both in terms of knowledge, attitudes and psychomotor. The case study conducted at Tangerang Regency General Hospital aims to explore the extent of the role of nurses in carrying out health education to patients in the context of health promotion in Tangerang District General Hospital. This case study was carried out by observing 66 nurses in 5 inpatient rooms at the Tangerang District General Hospital in the period October to December 2018. The researchers conducted field analysis using the Problem Solving for Better Health (PSBH) technique. The results of the PSBH found that nurses were not optimal in carrying out health education to patients. So researchers have disseminated health education to nurses. There is a need for directing efforts from managers to implement health education in hospitals on an ongoing basis according to the concepts that have been conveyed in dissemination, and it is expected that the Hospital Health Promotion institution will run in order to manage trained nurse educators.Keywords: Health education, Knowledge, Attitude, Psychomotor, Nurse